The Paradox of Averroes - Nur S. Kirabaev (RUDN Journal of Philosophy)
The research examines the problem of different ways of perceiving the ancient philosophical tradition in classical Arab Muslim and medieval European philosophy. It is noted that the difference in the ways of perception is determined, in particular, by the peculiarities of the concept of “knowledge” in Islam and Christianity. In the interaction between Arab Muslim and Christian cultures, stereotypes emerge in mutual perceptions, surprisingly leading to paradoxes like the Christianization and Europeanization of Eastern Peripatetic teachings. Their works were translated into Latin, and their names were "Latinized". The most famous names of philosophers: Ibn Sina (980-1037) is better known in Europe as Avicenna and Ibn Rushd (1126-1198) as Averroes. These thinkers belonged to the school of Eastern Peripateticism. Eastern Peripateticism or Eastern Aristotelianism are terms that denote one of the directions of Arab-Muslim philosophy of the Middle Ages. As is known, it is the representatives of Eastern Peripateticism that are called falasifa (الفلاسفة), and their teachings falsafah (فلسفة). In medieval Arab-Muslim culture, the term "falsafa" referred to ancient philosophy and the teachings of thinkers like al-Farabi (870-950), Ibn Sina, and Ibn Rushd, who were influenced by ancient philosophical models. Unlike European medieval philosophy, a unique aspect of falsafa was that it was neither regarded as nor aspired to be a servant of religion. It is with the name of Ibn Rushd that one of the directions of development of medieval European philosophy is associated - “Latin Averroism”, which as a philosophical term is applied to the direction in scholasticism of the XIII-th century, based on Averroes’ interpretation of Aristotle and underlies the doctrine of “dual truth”, which considered the independence of truths of reason from truths of revelation, and, ultimately, philosophy from religion. The main representatives of this movement were Siger of Brabant (c. 1240-1284) and Boethius of Dacia (c. 1240-1284). The essence of the paradox is that medieval Europe knew the teachings of Averroes but did not know the teachings of Ibn Rushd or perceived them in its own way. At the same time, the Arab East, as the birthplace of Ibn Rushd’s teachings, was not familiar with either the so-called Averroism or the concept of “dual truth”. In this context, the paradox can be explained as a situation that exists in historical reality, but does not have a strictly logical explanation, that is, at first glance, the authorship of Averroes as the creator of the doctrine of “dual truth” seems true, but in fact is an unreliable statement. This is also due to the fact that the concepts and value attitudes of one culture, transferred to explain the phenomena of another culture, form a stereotypical perception of the phenomena of this other culture. At the same time, within the framework of the interaction of cultures, the spread of “Latin Averroism” is one of the examples of the integration of the Arab-Muslim philosophical tradition into medieval European culture.